Effect of fungal pretreatment by Aspergillus niger assisted by ultrasonication on microfibrillated cellulose obtained from cocoa pod husk - ., Avicenna; Jimat, Dzun Noraini; Mohd Salleh, Hamzah; Anuar, Hazleen (Akademia Baru, 2016)
Microfibrillated cellulose (MFC) can be used in many industrial areas such as composites for construction, automotive, furniture and new materials for electronics and pharmaceutical applications as well as thickener in cosmetic products. It can be isolated from different lignocellulosic materials using numerous technologies. In this study, MFC was produced from cocoa pod husk (CPH) substrate in two distinct processes. Substrate was subjected to fungal-pretreatment at the first stage through a solid state fermentation by Aspergillus niger to promote enzymatic splitting of cellulose. The fungal pretreated substrate was then mechanically processed by the application of high-intensity ultrasonication. The optimum process of the fungal pretreatment stage through a response surface methodology (RSM) by employing central composite design (CCD) using Design expert version 8.0 with substrate raw particle size (RPS) inoculum size (IS) as independent variables were investigated. Statistical result of RSM showed that the model follows a quadratic response with IS as significant term. The 3D model graph exhibit an inverted peak response surface with maximum MFC particle size of 2761 nm at RPH of 850 µm and 5.0% IS. SEM images showed that the structure and morphology of the MFC differed over the various levels of IS with MFC diameter between 30 – 50 µm. Fungal-pretreatment was able to remove amorphous structure of hemicelluloses and lignin giving a loosen structure that less than 100m. FTIR analyses indicated a prominent spectra change between 3600 cm-1 and 2600 cm-1. The peak at approximately 1730 cm-1 of the raw substrate attributes to the presence of hemicellulose, which this spectra poses lower intensity and almost disappeared after the fungal treated samples were ultrasonicated. The appearance of 2θ = 150 for both treated MFC was also observed from XRD diffractograms which indicates the high content of crystalline cellulose.